(3QSGdI aj MQha GdYWa heYGfjgG hHYV eG jJYdb HgGs - (3eLghds
(3ChdgG (B:s
(3HjGf MQha GdYWa hCMcGegG JaUjdG bO PcQJ Mha GdLQ heG jJYdb HgG hdeG CfgjJ GdcdGe YdjgG CNPJ GdBf aj PcQ MQha GdYWa hHjGf eG jJYdb HgG aCbhd Ef MQha GdYWa YTQI ChdgG GdhGh GdYGWaI heYfGgG eWdbs
(3BNQgG (B:s
(3Ce eJUdI hGdJbOjQ CYdeJe Cf GdLfI MaJ HGdecGQg Ce MSHJe GfJgi eG JYdb NGWQj HLeYg ef MQha GdYWa heYGfjgG hHYV eG jJYdb HgGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs